A Normative Model For Sustainable Cultural And Heritage Tourism In Regional Development Of Southern Jalisco (Global Journal of Management and Business Research, 2012)
This study aims to propose a normative model to determine the potential of cultural tourism in the municipalities that comprise the region 6 of the State of Jalisco, territorially delimited in the South of Jalisco. Firstly, it is conducted an anlaysis to determine the demand for cultural tourism to determine the cultural tourist profile under the assumptions that tourists especially motivated by culture, tend to travel longer distances than most tourists. It discusses the motivations and satisfactions of cultural tourists to establish the potential market in accordance with the characteristics of the target market in the Southern region of Jalisco. Any operation of cultural tourism companies should make the strategic diagnosis, so that explains the use of SWOT analysis as a tool for strategic planning of cultural tourism enterprises. Finally, we propose the development strategies of cultural tourism in this region of Southern Jalisco.
Keywords: Regional development; tourism companies; Southern Jalisco; cultural tourism